STUDI FENOMENOLOGI IMPLIKASI KARAKTER GURU GENERASI Z TERHADAP INOVASI PENDIDIKAN BERBASIS TEKNOLOGI INFORMASI - Nanda Hanii; Nurul Alfiyah; Munawir Munawir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
People in Generation Z are those who were born and raised in the digital era, where various types of information technology have developed more and more sophisticated. In this way, it is hoped that the distinctive character of Generation Z teachers who are fluent in technology can create information technology-based educational innovations that are reflected in the learning process. This research aims to discuss the implications of the character of Generation Z teachers for information technology-based educational innovation. This research is a type of qualitative research using a phenomenological study approach. The focus of this research is the learning experiences and innovations of Generation Z teachers in integrating learning using information technology. The subject of this research is a teacher from an Islamic elementary school in Surabaya who is a Generation Z teacher. The data collection technique used in this research is an in-depth interview with a semi-structured interview type. The research results show that Generation Z teachers have created several educational innovations by implementing information technology-based learning platforms or applications for students during the learning process, namely the first is the Google Educational Resources on Artificial Intelligence (AL) platform which consists of several features, namely Google AL Experiments. Google AIY, Tensorflow Playground, Teachable Machine, Google What If, GAN Play, and APP Inventor. Both AL-Powered Application: Language Learning platforms, such as Duolingo and Orai. Meanwhile, platforms for teachers include Github, Python, Teaching AL in Primary Classroom, Microsost Course, and Curriculum Code.